Efficacy and safety of Shenxiong-Xinmaikang Decoction in patients with stable angina pectoris: a real-world prospective observational study - Yanchen Dong; Yanchen Dong; Yanchen Dong; Kaojuan Zeng; Yongzhen Liang; Yongzhen Liang; Guoping Xie; Donghui Liang; Donghui Liang (Frontiers in Pharmacology)
BackgroundShenxiong-Xinmaikang Decoction (SXXMKD), a modified traditional Chinese herbal formula, is widely used in clinical practice for stable angina pectoris (SAP). However, robust clinical evidence supporting its efficacy and safety is lacking. This study aimed to evaluate the real-world effectiveness and safety of SXXMKD as an adjunct to standard therapy for SAP.MethodsThis was a prospective, single-center, real-world observational study conducted between 2019 and 2023, enrolling 219 SAP patients (Registry: ChiCTR2100052872). Patients received either standard care alone (standard biomedical treatment group, SBMT group; n = 101) or SXXMKD combined with standard care (combined Traditional Chinese Medicine, CTCM group; n = 118). To minimize selection bias and balance baseline covariates, we applied inverse probability of treatment weighting (IPTW). Clinical outcomes were assessed at short- and long-term follow-up.ResultsAfter IPTW adjustment, baseline characteristics were well-balanced between the groups. Compared to the SBMT group, the CTCM group demonstrated significant improvements in angina symptom scores, electrocardiogram readings, and left ventricular ejection fraction (LVEF). Furthermore, the CTCM group showed lower levels of low-density lipoprotein cholesterol (LDL-C), creatine kinase (CK), high-sensitivity C-reactive protein (hs-CRP), and cardiac troponin I (cTnI). While the incidence of cardiovascular events was reduced in the CTCM group, the difference in cardiovascular event-free survival did not reach statistical significance.ConclusionIn a real-world setting, the addition of SXXMKD to standard biomedical treatment for SAP was safe and associated with improved symptomatic, functional, and biochemical outcomes. These findings suggest that SXXMKD is a promising adjunctive treatment for improving clinical outcomes in patients with stable angina.Clinical trial registrationhttps://www.chictr.org.cn/, identifier: ChiCTR2100052872.